Pulmonary hydatid cyst - A radiological challenge! - Kumar, N; Mishra, M; Singhal, A (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Hydatid disease is a parasitic infestation caused by Echinococcus granulosus. The resulting large cysts in the lung, a special clinical entity called giant hydatid cysts, is rare. Our case involves a middle-aged man who presented to us with vague chest complaints. Chest X-ray revealed a large cavity with an airfl uid level in the right hemithorax, which brought to the mind a constellation of differential diagnoses. A diagnosis of hydatid cyst was made intraoperatively. This case report provides evidence that radiological findings may be misleading and cause a diagnostic delay in such cases. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS 2012; IX (1) 39-42 DOI: http://dx.doi.org/10.3126/saarctb.v9i1.6964